2011
DOI: 10.1177/0149206310394186
|View full text |Cite
|
Sign up to set email alerts
|

The Internal and External Networks of Knowledge-Intensive Teams

Abstract: Using a sample of 56 science research teams, the authors examined (a) the relationships between qualities of team internal and external networks and team performance and (b) the moderating impact of task routineness on these relationships. The authors argued that the mixed empirical results of past studies investigating the relationship between internal networks and performance may be due partly to variations in task routineness and partly to the presence of curvilinear relationships between network qualities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 91 publications
(152 reference statements)
1
101
1
1
Order By: Relevance
“…In contrast to other studies (e.g., [11,29]) where task non-routineness was found to be a moderator, we neither found a significant main effect on team performance nor any significant interaction effect. Interview data suggests that dedicated meetings help to achieve shared understanding and hence facilitate the accessing of knowledge to solve new tasks.…”
Section: Knowledge Application 51contrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to other studies (e.g., [11,29]) where task non-routineness was found to be a moderator, we neither found a significant main effect on team performance nor any significant interaction effect. Interview data suggests that dedicated meetings help to achieve shared understanding and hence facilitate the accessing of knowledge to solve new tasks.…”
Section: Knowledge Application 51contrasting
confidence: 99%
“…The rationale for the chosen criteria was, respectively, 1) to ensure sufficient knowledge of the organizational context and criterion 2) to learn from good practices. Criterion 3) was chosen because HC and COM had a similar distribution in task non-routines in the quantitative study, which is a frequently used factor (e.g., [10,11,29]) and the key informants were able to identify relevant participants. From each organization we selected four people who are primarily engaged in routine tasks and four people who are primarily engaged in non-routine tasks, leading to four focus groups in total.…”
Section: Focus Group Interviews 33mentioning
confidence: 99%
“…The importance of external knowledge sources to R&D teams is supported by research showing that R&D teams with stronger external network ties are more productive (Chung & Jackson, 2013).…”
Section: Team Knowledge Acquisition and Team Knowledge Sharingmentioning
confidence: 97%
“…Through collaborative interactions, team members and the team as a whole can acquire and share new and valuable knowledge. In addition, a team can increase its chance to make contact with knowledge sources by selecting members who have good interpersonal relationships with people within and outside the organization (Chung & Jackson, 2013). Further, adaptation skills help the team recognize dynamic conditions and respond to them by continuously searching for new information and knowledge (LePine, Colquitt, & Erez, 2000).…”
Section: Competency-enhancing Hr Practices For Knowledge-intensive Tementioning
confidence: 99%
“…Consequently, team leaders feel unsatisfied with their existing knowledge, which triggers the need for additional information (Wang et al, 2014), even for directive leaders who are used to structure team members' work , not to consult them. However, research has shown that consulting additional knowledge sources is instrumental in dealing with non-routine situations (Chung & Jackson, 2013;Jehn, 1995;Van de Ven et al, 1976). Empowering leaders are used to consult with subordinates and evaluate their opinions (Yukl, 2010).…”
Section: Routine Versus Non-routine: Environmental Situation As a Modmentioning
confidence: 99%